FAKTOR -FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PEMBELIAN MAKANAN JAJAN TRADISIONAL DI KOTA MALANG - Yuliati, Uci (Department of Management, 2011)
Fakultas Ekonomi Universitas Muhamadiyah MalangE-mail: uci@umm.ac.idABSTRACTThis research title is The Buying Factors Considered by Consummers On Traditional Cake inMalang City. Its aim is to learn buying factors considered by Malang residents in traditional cakes'consumption. All respondents are Malang residents who have been ever buying and consummingtraditional cake at market in Malang city. The result of research shows that there are 8 buying factorsconsidered in traditional cake consumption, namely personality (First Factor), price, promotion,javanese culture, knowledge, place, experience and life style. Based on the result, it can beconcluded tha the most buying factors considered is personality, namely education, age, job, gender,motivation, grand mother/fathers' custom and family custom.Keyword : buying factors